2016
DOI: 10.1080/13510002.2016.1215643
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia, oxidative stress and inflammatory markers

Abstract: This study provided further evidence that inflammatory and oxidative stress biomarkers may contribute to diagnostic information associated with preclinical increases in BGL. Further we have provided a unique study in the analysis of ratios of inflammatory biomarkers and correlations with increasing BGL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 66 publications
1
39
0
5
Order By: Relevance
“…Similar findings were reported in earlier studies which also demonstrated higher MDA levels and depleted glutathione content in newly diagnosed diabetes patients and. Lower level of GSH was reported in patients with hyperglycaemia . SOD levels in newly detected cases of diabetes were reported to be high in few studies and low in a few others …”
Section: Discussionmentioning
confidence: 92%
“…Similar findings were reported in earlier studies which also demonstrated higher MDA levels and depleted glutathione content in newly diagnosed diabetes patients and. Lower level of GSH was reported in patients with hyperglycaemia . SOD levels in newly detected cases of diabetes were reported to be high in few studies and low in a few others …”
Section: Discussionmentioning
confidence: 92%
“…IL-6 was significantly elevated in the prediabetes groups compared with the control group, whereas no such difference was observed between the prediabetes subgroups. IL-6 has exhibited no significant variation between the prediabetes groups and controls [53]. However, increased IL-6, another proinflammatory marker, is observed in hyperglycemic/hyperinsulinemic conditions [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…At presentation, type 2 diabetes is most often accompanied by other comorbidities including overweight/obesity, insulin resistance, hypertension and dyslipidaemia, features which are less common in type 1 diabetes at diagnosis, but which may occur as complications of type 1 diabetes later in the course of the disease. Oxidative stress and inflammation are implicated in both type 1 and type 2 diabetes; however, research has shown that these metabolic disturbances are very pronounced in type 2 diabetes (40)(41)(42)(43)(44) . The oxidative stress, inflammation, adiposity and dyslipidaemia which characterise diabetes may have independent relationships with MPOD, and therefore constitute plausible causal mechanisms in diabetic eye disease.…”
Section: Diabetes Mellitusmentioning
confidence: 99%